2019
DOI: 10.14246/irspsd.7.1_83
|View full text |Cite
|
Sign up to set email alerts
|

Categorizing Types of Transition Areas in Biosphere Reserves: a Case Study of the Baekdudaegan Mountain Ranges in South Korea

Abstract: The biosphere reserves (BRs) of the UNESCO's Man and the Biosphere Programme (MAB) aim at the successful coexistence of humans and nature. The existing BRs have worked with local people to create culture landscapes and conserve natural resources. The ideal BR models for areas undergoing climate change are cities within nature, and the areas that can be designated as BRs have natural and cultural landscapes. BRs comprise three areas, the core, buffer, and transition, in order to efficiently perform three functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Kim et al [27] reported that perceptions of the degree of unsafety were higher (48-57%) among residents of eastern and mountainous areas, which are affected annually by sediment and flooding disasters caused by typhoons and heavy rainfall, than among western residents (38-46%). Min et al [28] also explained that the living zone for residents was located in the watershed, and a provincial area was formed by the boundary of the mountainous region. In addition, most of the heavy rainfall occurs primarily in the summer season (June-September) as a result of the East Asian monsoon, during which time the Korean Peninsula is also impacted by the passage of severe tropical typhoons [29].…”
Section: Introductionmentioning
confidence: 99%
“…Kim et al [27] reported that perceptions of the degree of unsafety were higher (48-57%) among residents of eastern and mountainous areas, which are affected annually by sediment and flooding disasters caused by typhoons and heavy rainfall, than among western residents (38-46%). Min et al [28] also explained that the living zone for residents was located in the watershed, and a provincial area was formed by the boundary of the mountainous region. In addition, most of the heavy rainfall occurs primarily in the summer season (June-September) as a result of the East Asian monsoon, during which time the Korean Peninsula is also impacted by the passage of severe tropical typhoons [29].…”
Section: Introductionmentioning
confidence: 99%